Myofibroblasts - Hinz, Boris (Experimental eye research, 2016)
Myofibroblasts are activated in response to tissue injury with the primary task to repair lost or damaged extracellular matrix. Enhanced collagen secretion and subsequent contraction – scarring – are part of the normal wound healing response and crucial to restore tissue integrity. Due to myofibroblasts ability to repair but not regenerate, accumulation of scar tissue is always associated with reduced organ performance. This is a fair price to pay by the body for not falling apart. Whereas myofibroblasts typically vanish after successful repair, dysregulation of the normal repair process can lead to persistent myofibroblast activation, for instance by chronic inflammation or mechanical stress in the tissue. Excessive repair leads to the accumulation of stiff collagenous ECM contractures – fibrosis – with dramatic consequences for organ function. The clinical need to terminate detrimental myofibroblast activities has stimulated researchers to answer a number of essential questions: where do myofibroblasts come from, what are the factors leading to their activation, how do we discriminate myofibroblasts from other cells, what is the molecular basis for their contractile activity, and how can we stop or at least control them? This article reviews the current state of the myofibroblast literature by emphasizing their role in ocular repair and fibrosis. It appears that although the eye is quite an extraordinary organ, ocular myofibroblasts behave or misbehave just like their siblings in other organs. •Myofibroblasts are defined as contractile and collagen-secreting cells.•Myofibroblasts are activated from various precursors to repair damaged tissue.•Persistent myofibroblast activation results in accumulation of scar tissue – fibrosis.•Ocular precursors are keratocytes, epithelial, endothelial, lamina cribrosa and Müller cells.•Eye myofibroblasts are activated and controlled like myofibroblasts in other organs.